2012
DOI: 10.1037/a0026370
|View full text |Cite
|
Sign up to set email alerts
|

Elevated ambitions for fame among persons diagnosed with bipolar I disorder.

Abstract: A growing body of evidence suggests that people with bipolar disorder are highly goal-oriented. Compared to other persons, they expend more effort to attain rewards and view goal pursuit as more important to their self-worth. Persons at risk for mania and those diagnosed with bipolar spectrum disorders have been shown to endorse highly ambitious life goals, such as becoming a multimillionaire or achieving fame. This study is the first examination of whether such elevated goals characterize persons diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 51 publications
2
58
0
Order By: Relevance
“…Both depressive and manic mood states have been associated with dysfunctions of the brain reward system (Alloy et al, 2012;Hasler, 2006;Johnson et al, 2012b). Previous studies have shown that bipolar patients exhibit increased behavioral and emotional responses to reward or its anticipation compared with healthy controls (Alloy et al, 2012;Gruber, 2011;Johnson et al, 2012aJohnson et al, , 2012b. However, bipolar patients do not appear to be faster to learn stimulus-reward associations (Johnson et al, 2012b;O'Sullivan et al, 2011) and even exhibit deficits in probabilistic reversal learning compared with healthy controls (Dickstein et al, 2010;Gorrindo et al, 2005).…”
Section: Introductionmentioning
confidence: 88%
“…Both depressive and manic mood states have been associated with dysfunctions of the brain reward system (Alloy et al, 2012;Hasler, 2006;Johnson et al, 2012b). Previous studies have shown that bipolar patients exhibit increased behavioral and emotional responses to reward or its anticipation compared with healthy controls (Alloy et al, 2012;Gruber, 2011;Johnson et al, 2012aJohnson et al, , 2012b. However, bipolar patients do not appear to be faster to learn stimulus-reward associations (Johnson et al, 2012b;O'Sullivan et al, 2011) and even exhibit deficits in probabilistic reversal learning compared with healthy controls (Dickstein et al, 2010;Gorrindo et al, 2005).…”
Section: Introductionmentioning
confidence: 88%
“…Not only achievementrelated events but also social situations may trigger changes in mood in BD. For example Johnson, Carver, and Gotlib (2012) reported that individuals with BD show higher ambition for popular fame which on the one hand can be achievement-related, but is essentially a social recognition of a special role or status. P. Gilbert, McEwan, Hay, Irons, and Cheung (2007) found substantial associations between mood in BD and feelings of superiority or inferiority.…”
Section: Bipolar Disorder and Social Comparisonsmentioning
confidence: 97%
“…In line with this hypothesis, euthymic bipolar individuals have been found to exhibit a distinctive profile of cognitive styles characterized by perfectionism, self-criticism and autonomy rather than the dependency and approval-seeking styles observed among unipolar depressed individuals 1 . Additionally, controlling for current mood symptoms, individuals with BSDs exhibit higher achievement motivation, goal-attainment dysfunctional attitudes (e.g., "A person should do well at everything") and ambitious goal-striving styles than controls 1,2 .…”
mentioning
confidence: 99%
“…In the US, fragmentation across health agencies, state departments, and local bureaucracies, together with a lack of ownership of systematic risk surveillance by health systems, all but ensure that almost no family at risk ever receives this level of support. The end result is that child maltreatment is perpetrated at epidemic proportions: a conservative estimate of prevalence based on official records is that, in the US, one out of every six children is a victim 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation